Preparation method of anti-warping coating liquid, random crack template and electromagnetic shielding optical window

By adding N-methylpyrrolidone to the aqueous acrylic resin, it improves its fluidity and ductility, and solves the problems of film warping and crack unevenness, and a high-quality random crack template was prepared and used for electromagnetic shielding optical windows, which satisfies the Highly demanding application performance.

CN117004282BActive Publication Date: 2024-12-17XIAN INST OF OPTICS & PRECISION MECHANICS CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310678613.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-08
Publication Date
2024-12-17
Estimated Expiration
2043-06-08

AI Technical Summary

Technical Problem

The aqueous acrylic resin has a high shrinkage rate during drying, resulting in uneven film warping and crack width, which cannot meet the application of high light transmittance, conductivity or imaging quality requirements.

Method used

Anti-warping coating liquid containing N-methylpyrrolidone (NMP) as dispersant is used to adjust the monomer ratio and process conditions to increase the fluidity and ductility of the acrylic resin, and reduce the difference in the drying rate of the coating surface layer. , improve coating adhesion, prepare random crack templates and plate metal grids therein.

Benefits of technology

It effectively reduces the degree of warpage of the coating, improves crack unevenness, improves the quality of random crack templates, and meets high requirements for applications in the fields of film electrodes, precision electronic devices and glass light window defogging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004275711170000101
    Figure BDA0004275711170000101
  • Figure HDA0004275711190000011
    Figure HDA0004275711190000011
  • Figure HDA0004275711190000021
    Figure HDA0004275711190000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of coatings, and specifically discloses a method for preparing an anti-warping coating liquid, a random crack template, and an optical window. The disclosed anti-warping coating liquid uses N-methylpyrrolidone as a dispersant, and by adding NMP during the preparation of an aqueous acrylic resin, the fluidity and ductility of the acrylic resin are increased, the difference in drying rate between the surface areas of the coating is reduced, and the adhesion between the coating and the substrate is improved. The method for preparing the random crack template and the electromagnetic shielding optical window is prepared using the masking liquid of the present invention. The present invention can effectively solve the problem of uneven warping cracks of random crack templates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a masking liquid for preparing an electromagnetic shielding optical window and a preparation method of a corresponding random crack template and an electromagnetic shielding optical window. Background Art

[0002] Waterborne acrylic resin is an important polymer material, which is widely used in the fields of coating, optics, electronics, etc., such as thin film electrodes, crack paint, optical window materials, and precision electronic devices. When preparing waterborne acrylic resin film, the acrylic resin coating liquid is usually coated on the substrate by solution dipping or coating, and then the acrylic resin coating is fixed on the substrate by drying.

[0003] However, due to the large shrinkage rate of water-based acrylic resin during drying, it is easy to cause warping of the film and uneven crack width, thereby affecting the quality and application performance of the film. The acrylic resin system used in the prior art is usually made of acrylic acid and acrylic acid monomers, emulsifiers, initiators and buffers through low-temperature polymerization, which can meet the needs of decorative coating applications, but for thin-film electrodes, optical window materials, precision electronic devices, and glass window defogging applications with relatively high light transmittance, conductivity or imaging quality requirements, it cannot meet the requirements due to the uneven crack width of the random crack template and the serious warping of the crack edge. Summary of the invention

[0004] In view of the defects or shortcomings of the prior art, the present invention provides an anti-warping coating liquid.

[0005] To this end, the anti-warping coating liquid provided by the present invention comprises, by weight, 40-60 parts of water, 20-40 parts of hard monomers, less than 20 parts of soft monomers, 2-10 parts of functional monomers, 0.1-0.5 parts of initiators, 1-5 parts of emulsifiers, 0.5-1 parts of buffers, and 0.5-2 parts of dispersants;

[0006] The hard monomer is selected from one or more of methyl methacrylate (MMA), styrene (ST), acrylonitrile (AN), acrylamide, methyl acrylate and vinyl acetate (VAC);

[0007] The soft monomer is selected from one or more of butyl acrylate (BA), ethyl acrylate (EA) and isooctyl acrylate (2-EHA);

[0008] The functional monomer is selected from one or more of hydroxypropyl acrylate (HPA), hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxyethyl methacrylate, acrylic acid (AA), methacrylic acid, diacetone acrylamide, glycidyl methacrylate, maleic anhydride, trimethylamineethyl methacrylate and N-hydroxymethyl acrylamide;

[0009] The initiator is selected from one or more of ammonium persulfate (APS), potassium persulfate (KPS), sodium persulfate (NPS), hydrogen peroxide, dibenzoyl peroxide (BPO), tert-butyl perbenzoate, azobisisobutyronitrile (AIBN) and azobisisoheptanenitrile (ABVN);

[0010] The emulsifier is selected from anionic emulsifiers and / or nonionic emulsifiers; the anionic emulsifier is selected from one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and rosin soap; the nonionic emulsifier is selected from one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty amine polyoxyethylene ether, alkyl alcoholamine polyoxyethylene ether, octylphenol ethoxylate, phenylphenol ethoxylate and polyoxyethylene sorbitan fatty acid ester;

[0011] The buffer is selected from one or more of sodium bicarbonate, sodium dihydrogen carbonate and sodium acetate;

[0012] The dispersant is N-methylpyrrolidone (NMP).

[0013] The present invention also provides a method for preparing the above-mentioned anti-warping coating liquid. The provided preparation method comprises:

[0014] (1) mixing a hard monomer, a soft monomer, a functional monomer and a dispersant to obtain a monomer mixture;

[0015] (2) dissolving an emulsifier, a buffer and a portion of the monomer mixture in water to obtain an emulsified mixture;

[0016] (3) heating the emulsified mixture to 50-75° C. and adding a portion of the initiator aqueous solution during stirring to obtain a mixture 1;

[0017] (4) heating the mixture 1 to 75-85° C., and then dropping the remaining monomer mixture and the remaining initiator aqueous solution into the mixture 1 to obtain a mixture 2;

[0018] (5) The mixture 2 is reacted at 85-90° C. and then cooled to room temperature. The pH value is then adjusted to neutral and filtered to obtain a coating solution.

[0019] An optional solution is to use a 300-500 mesh filter cloth for filtering in step (5).

[0020] The present invention also provides a method for preparing a random crack template. The method comprises spin coating the coating liquid on the surface of an optical window substrate to form a mask layer, and then placing the optical window coated with the mask layer in a temperature and humidity environment for drying, thereby generating random cracks on the surface mask layer.

[0021] The optional solution is that the spin coating process conditions are temperature 15-30°C, humidity 40%-45%, and spin coating speed 600-800r / min. The temperature and humidity environment is: temperature 15-30°C, humidity set to 30%-70%RH; drying time 10-18h. The mask layer thickness is 5-20 microns.

[0022] Furthermore, the average width of the random cracks is less than or equal to 3.5 μm; the crack void ratio is:

[0023] 8.0%-10.0%; the average grid size of random cracks is: 50.0-80.0μm. The crack edge warping is 0.1-0.6μm, and cracks with a width of 2-4μm account for more than 60%.

[0024] The present invention also provides a method for preparing a metal grid electromagnetic shielding optical window. The method for preparing a metal grid electromagnetic shielding optical window comprises preparing a random crack template by the above method, then plating metal in the random cracks on the surface of the random crack template, and then removing the mask to prepare a metal grid electromagnetic shielding optical window. Optionally, the metal is selected from Cu, Ag, Au, Al or Ni.

[0025] Compared with the prior art, the anti-warpage coating liquid of the present invention uses N-methylpyrrolidone (NMP) as a dispersant. By adding NMP during the preparation of the water-based acrylic resin, the fluidity and ductility of the acrylic resin are increased, the difference in drying rate between the surface areas of the coating is reduced, and the adhesion between the coating and the substrate is improved, which can effectively reduce the degree of warpage of the coating, improve the crack unevenness, and improve the quality of the random crack template. In addition, the coating liquid of the present invention can also be used in technical fields such as thin film electrodes, precision electronic devices, and glass window defogging. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The optical micrograph of the random crack template prepared in Example 1 of the present invention (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0027] Figure 2The optical micrograph of the random crack template prepared in Example 2 of the present invention (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0028] Figure 3 The optical micrograph of the random crack template prepared in Example 3 of the present invention (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0029] Figure 4 The optical micrograph of the random crack template prepared in Example 4 of the present invention (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0030] Figure 5 This is a graph of the light transmittance of the quartz light window before and after the plated metal grid prepared in Example 5 of the present invention;

[0031] Figure 6 The electromagnetic shielding performance test results of the quartz window prepared in Example 5 of the present invention;

[0032] Figure 7 The optical micrograph of the random crack template prepared in Comparative Example 1 (a, the scale in the lower right corner of the figure is 50 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0033] Figure 8 The optical micrograph of the random crack template prepared in Comparative Example 2 (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface);

[0034] Fig. 9 The optical micrograph of the random crack template prepared in Comparative Example 3 (a, the scale in the lower right corner of the figure is 100 μm) and the laser confocal microscopy test result figure (b, the color change in the figure indicates: the height change of the random crack template surface); DETAILED DESCRIPTION

[0035] Unless otherwise specified, the scientific and technical terms in this article are understood according to the knowledge of ordinary technicians in the relevant fields. It should be noted that based on the scheme of the present invention, those skilled in the art can optimize the methods of the present invention, including but not limited to the components, the ratio of the components, the temperature and duration, the order and method of adding the components, the mixing method, etc., to achieve the effect of the present invention.

[0036] The optical window substrate described herein can be made of a substrate that meets the performance requirements of an optical fiber window, such as, but not limited to, fused silica glass, ordinary optical glass such as K9, radiation-resistant optical glass, colored optical glass, float glass, fluoropotassium salt mid-infrared glass, and mid-infrared and long-wave infrared transparent silicon single crystal, germanium single crystal, sapphire crystal, fluoride crystal, zinc sulfide / zinc selenide crystal or polycrystalline optical material substrate. The following embodiments take quartz glass as an example of an optical window substrate to explain the present invention.

[0037] The average mesh size (i.e., mesh width) and average crack width detection methods described in the following embodiments and comparative examples are: After testing with an optical microscope, the crack width data (500 / m 2 ), grid size data (500 / m 2 ) are counted and the corresponding average value is obtained. The detection method of the proportion of cracks with a width of 2-4μm (used to evaluate the uniformity of crack width) is: after testing with an optical microscope, the crack width data of multiple different parts (500 / m 2 ) was obtained by statistical analysis. The crack void ratio was calculated by Matlab software image recognition. The crack edge warping detection methods are as follows: a laser confocal microscope was used to measure the warping degree of the water-based anti-warping acrylic resin film layer.

[0038] The components used in the following examples and comparative examples are all commercially available products.

[0039] Embodiment 1:

[0040] The coating liquid formula of this embodiment is: 55 parts of deionized water, 25 parts of hard monomer, 15 parts of soft monomer, 5 parts of functional monomer, 0.2 parts of initiator, 2 parts of emulsifier, 0.7 parts of buffer, and 0.6 parts of dispersant N-methylpyrrolidone;

[0041] Among them, the hard monomer is methyl methacrylate;

[0042] The soft elastomer is made of butyl acrylate;

[0043] The functional monomers are acrylic acid and hydroxypropyl acrylate, and the mass ratio of acrylic acid to hydroxypropyl acrylate is 2:3;

[0044] The initiator is ammonium persulfate;

[0045] The emulsifier is selected from sodium dodecyl sulfonate and alkylphenol polyoxyethylene ether, and the mass ratio of sodium dodecyl sulfonate to alkylphenol polyoxyethylene ether is 1:2;

[0046] The buffer is sodium bicarbonate;

[0047] The coating solution preparation method of this embodiment is:

[0048] (1) mixing a hard monomer, a soft monomer, a functional monomer and a dispersant to obtain a monomer mixture; and dissolving an initiator in 20 parts by weight of deionized water to obtain an initiator aqueous solution;

[0049] (2) dissolving an emulsifier, a buffer and 15 wt % of a monomer mixture in 35 parts by weight of water, and mixing them by magnetic stirring (1000 rpm) to obtain an emulsified mixture;

[0050] (3) heating the emulsified mixture to 65±5° C., then adding 18 wt % initiator aqueous solution while stirring to obtain a mixture 1;

[0051] (4) heating the mixture 1 to 70±5° C., stirring continuously for 30 min, and then dropping the remaining monomer mixture and the initiator aqueous solution into the mixture 1 (the dropping is completed within 3 h), to obtain a mixture 2;

[0052] (5) Mixture 2 was stirred and reacted at 80±5° C. for 2 h, and then the reactant was cooled to room temperature and an appropriate amount of ammonia was added to adjust the pH to neutral. The mixture was then filtered three times using a 500-mesh filter cloth to obtain a coating solution.

[0053] A spin coater (KW-4T) was further used, with a rotation speed of 800 r / min, at room temperature and a humidity of 40%, to spin coat the coating solution prepared in this embodiment on a clean, 1 mm thick optical window quartz glass for 50 s to obtain a mask layer with a thickness of about 15 μm.

[0054] The optical window glass covered with the mask layer coated above was placed in a temperature and humidity chamber, the temperature was set to 25°C, the humidity was set to 45%, and the time was controlled to be 12 hours; the random crack mask formed was as follows Figure 1 As shown in (a), the average grid size is 53.6 μm, the average crack width is 2.47 μm, and the random crack mask with good connectivity has a crack width of 2-4 μm accounting for 63.3% and a crack duty ratio of 9.11%. The laser confocal microscopy test results of the random crack mask are shown in Figure 1 As shown in (b), the crack edge warping is 0.63 μm.

[0055] Embodiment 2:

[0056] The difference from Example 1 is that the amount of dispersant used is different: 0.9 parts of N-methylpyrrolidone.

[0057] The random crack mask formed in this embodiment is as follows: Figure 2As shown in (a), the average grid size is 54.2 μm, the average crack width is 2.56 μm, and the random crack mask with good connectivity has a crack width of 2-4 μm accounting for 67.4% and a crack duty ratio of 9.32%. The laser confocal microscopy test results of the formed random crack mask are shown in Figure 2 As shown in (b), the crack edge warping is 0.33 μm.

[0058] Embodiment 3:

[0059] The difference from Example 1 is that the amount of dispersant used is different: 1.2 parts of N-methylpyrrolidone.

[0060] The random crack mask formed is as follows Figure 3 As shown in (a), the average grid size is 52.6 μm, the average crack width is 2.44 μm, and the random crack mask with good connectivity has a crack width of 2-4 μm accounting for 72.1% and a crack duty ratio of 9.16%. The laser confocal microscopy test results of the formed random crack mask are shown in Figure 3 As shown in (b), the crack edge warping is 0.23 μm.

[0061] Embodiment 4:

[0062] The difference from Example 1 is that the amount of dispersant used is different: 1.5 parts of N-methylpyrrolidone.

[0063] The random crack mask formed is as follows Figure 4 As shown in (a), the average grid size is 52.1 μm, the average crack width is 2.51 μm, and the random crack mask with good connectivity has a crack width of 2-4 μm accounting for 65.6% and a crack duty ratio of 9.50%. The laser confocal microscopy test results of the formed random crack mask are shown in Figure 4 As shown in (b), the crack edge warping is 0.58 μm.

[0064] Embodiment 5:

[0065] Electromagnetic shielding optical windows are core functional components that ensure the normal operation of optoelectronic instruments and equipment in microwave and electromagnetic pulse radiation environments, such as electronic instrument display screens, aircraft and vehicle windows, and photoelectric detector systems.

[0066] Metal grid type electromagnetic shielding optical window is a transparent optical window device that attenuates electromagnetic wave radiation through metal grid. The method of achieving electromagnetic shielding performance of metal grid type electromagnetic shielding optical window is mainly to plate a metal grid with good conductive performance on an optical glass substrate.

[0067] For metal grids with irregular shapes and structures, a random crack template method is usually used for preparation. The random crack template preparation method is to apply a coating liquid on the light window substrate material to form a coating layer (mask layer). After the coating layer dries and cracks, suitable cracks will be generated on the surface of the light window substrate material (including several cracks of different lengths, and several cracks of different lengths are randomly distributed to form multiple grids), thereby forming a random crack template. After the metal grid is plated in the cracks of the random crack template and the coating layer is removed, it becomes a template for the plated metal grid.

[0068] This embodiment adopts ion source assisted evaporation method (ion source anode voltage 200V, anode current 1.5A, argon partial pressure 3.0×10 -3 Pa, argon flow rate 10 sccm), random metal Cu grids were plated using the coating solutions of Example 2 and Example 3, respectively, to prepare random metal copper grids, and to make metal grid electromagnetic shielding optical windows.

[0069] Afterwards, a four-probe tester was used to test the square resistance of the optical window made in this embodiment. The square resistances of the samples in Embodiment 2 and Embodiment 3 were 2.57Ω / sq ​​and 2.83Ω / sq, respectively. Compared with the relevant provisions in GB / T26598-2011, the metal lines of the grid on the surface of the samples obtained in the above embodiments had good connectivity.

[0070] The transmittance of the samples was tested using a UV-visible spectrophotometer. Figure 5 As shown, the absolute transmittances of Example 2 and Example 3 in the visible light band are approximately 86.1% and 86.6%, respectively. Compared with the relevant provisions in GB / T26598-2011, the light transmission performance is good.

[0071] At the same time, the flange coaxial method was used to test the electromagnetic shielding capabilities of the two samples of this embodiment. Figure 6 As shown, the test results show that when the electromagnetic wave frequency is 1-3 GHz, the average electromagnetic shielding effectiveness of Example 2 and Example 3 are 36.0 dB and 33.5 dB respectively; when the electromagnetic wave frequency is 3-18 GHz, the average electromagnetic shielding effectiveness of Example 2 and Example 3 are 27.9 dB and 27.8 dB respectively. Compared with the relevant provisions in GB / T 35575-2017, the electromagnetic shielding performance of the obtained window is excellent.

[0072] Comparative Example 1:

[0073] The difference between this comparative example and Example 1 is that the dispersant is replaced by glycerol; the rest is the same as Example 1.

[0074] The random crack mask prepared in this comparative example is as follows Figure 7As shown in (a), the average grid size is 63.4 μm, the average crack width is 2.83 μm, and the random crack mask with good connectivity has a crack width of 2-4 μm accounting for 70.3% and a crack duty ratio of 8.83%. The laser confocal microscopy test results of the formed random crack mask are shown in Figure 7 As shown in (b), the crack edge warping is 1.12 μm.

[0075] Comparative Example 2:

[0076] The difference between this comparative example and Example 1 is that the dispersant is replaced by ethylene glycol; the rest is the same as Example 1.

[0077] The random crack mask prepared in this comparative example is as follows Figure 8 (a) shows that the average grid size is 60.5 μm, the average crack width is 2.72 μm, and the random crack mask has good connectivity. The cracks with a width of 2-4 μm account for 68.9% and the crack duty ratio is 8.89%. The laser confocal microscopy test results of the random crack mask are shown in Figure 8 As shown in (b), the crack edge warping is 0.77 μm.

[0078] Comparative Example 3:

[0079] The difference between this comparative example and Example 1 is that no dispersant is added; the rest is the same as Example 1.

[0080] The random crack mask made in this comparative example is Fig. 9 (a) shows that the average grid size is 71.9 μm, the average crack width is 3.15 μm, and the random crack mask has good connectivity. The cracks with a width of 2-4 μm account for 60.3% and the crack duty ratio is 8.67%. The laser confocal microscopy test results of the random crack mask are shown in Fig. 9 As shown in (b), the crack edge warping is 1.52 μm.

[0081] The test results of the random crack mask of the above embodiment and comparative example are shown in Table 1 below:

[0082] Table 1

[0083]

[0084] The data in Table 1 show that, relative to the comparative examples, the crack edge warping of Examples 1-4 is smaller. Meanwhile, relative to Comparative Example 3, the cracks with a width of 2-4 μm in Examples 1-4 account for a larger proportion. This indicates that the addition of NMP during the preparation of the water-based acrylic resin can increase the fluidity and ductility of the water-based acrylic resin, reduce the difference in drying rate between the surface areas of the coating, and improve the adhesion between the coating and the substrate, thereby effectively reducing the warping degree of the coating and improving the crack unevenness.

[0085] The water content of the water-based acrylic resin film is high, and the solvent evaporates quickly during the drying process, resulting in a large stress difference between the inside and the surface of the film, which leads to excessive cracking of the film. At the same time, the large stress difference formed between the inside and the surface of the film will also cause the film to separate from the substrate, that is, the film warps. It can be seen from the above embodiments and comparative examples that adding N-methylpyrrolidone during the preparation of the coating solution not only improves the problem of crack unevenness, but also effectively reduces the degree of warping of the coating and improves the quality of the random crack template.

Claims

1. An anti-warping coating liquid, characterized in that: The raw materials for preparing the coating solution include, by weight, 40 to 60 parts of water, 20 to 40 parts of hard monomers, less than 20 parts of soft monomers, 2 to 10 parts of functional monomers, 0.1 to 0.5 parts of initiators, 1 to 5 parts of emulsifiers, 0.5 to 1 parts of buffers, and 0.5 to 2 parts of dispersants; The hard monomer is selected from one or more of methyl methacrylate, styrene, acrylonitrile, acrylamide, methyl acrylate and vinyl acetate; The soft monomer is selected from one or more of butyl acrylate, ethyl acrylate and isooctyl acrylate; The functional monomer is selected from one or more of hydroxypropyl acrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, hydroxyethyl methacrylate, acrylic acid, methacrylic acid, diacetone acrylamide, glycidyl methacrylate, maleic anhydride, trimethylamineethyl methacrylate and N-hydroxymethyl acrylamide; The initiator is selected from one or more of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, dibenzoyl peroxide, tert-butyl perbenzoate, azobisisobutyronitrile and azobisisoheptanenitrile; The emulsifier is selected from anionic emulsifiers and / or nonionic emulsifiers; the anionic emulsifier is selected from one or more of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and rosin soap; the nonionic emulsifier is selected from one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty amine polyoxyethylene ether, alkyl alcohol amine polyoxyethylene ether, octylphenol ethoxylate, nonylphenol ethoxylate and polyoxyethylene sorbitan fatty acid ester; The buffer is selected from one or more of sodium bicarbonate, sodium dihydrogen carbonate and sodium acetate; The dispersant is N-methylpyrrolidone.

2. The method for preparing the anti-warping coating liquid according to claim 1, characterized in that the method include: (1) mixing a hard monomer, a soft monomer, a functional monomer and a dispersant to obtain a monomer mixture; (2) dissolving an emulsifier, a buffer and a portion of the monomer mixture in water to obtain an emulsified mixture; (3) heating the emulsified mixture to 50-75° C. and adding a portion of the initiator aqueous solution during stirring to obtain a mixture 1; (4) heating the mixture 1 to 75-85° C., and then dropping the remaining monomer mixture and the remaining initiator aqueous solution into the mixture 1 to obtain a mixture 2; (5) The mixture 2 is reacted at 85-90° C. and then cooled to room temperature. The pH value is then adjusted to neutral and filtered to obtain a coating solution.

3. The method for preparing the anti-warping coating liquid according to claim 2, characterized in that: In step (5), 300-500 mesh filter cloth is used for filtering.

4. A method for preparing a random crack template, characterized in that: The method comprises spin coating the coating liquid of claim 1 or 2 on the surface of an optical window substrate to form a mask layer, and then placing the optical window coated with the mask layer in a temperature and humidity environment for drying, thereby generating random cracks on the surface mask layer.

5. The method for preparing a random crack template according to claim 4, characterized in that: The spin coating process conditions are as follows: temperature of 15-30° C., humidity of 40%-45%, and a spin coating speed of 600-800 r / min.

6. The method for preparing a random crack template according to claim 4, characterized in that: The temperature and humidity environment is as follows: the temperature is 15-30° C., the humidity is set to 30%-70% RH; and the drying time is 10-18 hours.

7. The method for preparing a random crack template according to claim 4, characterized in that: The thickness of the mask layer is 5 to 20 microns.

8. The method for preparing a random crack template according to claim 4, characterized in that: The average width of the random cracks is less than or equal to 3.5 μm; the crack void ratio is 8.0% to 10.0%; and the average grid size of the random cracks is 50.0 to 80.0 μm.

9. The method for preparing a random crack template according to claim 4, characterized in that: The warping of the crack edge is 0.1-0.6 μm, and cracks with a width of 2-4 μm account for more than 60%.

10. A method for preparing a metal grid electromagnetic shielding optical window, characterized in that: A random crack template is prepared by the method described in any one of claims 4 to 9, and then metal is plated in the random cracks on the surface of the random crack template, and then the mask is removed to prepare a metal grid electromagnetic shielding optical window.

11. The method for preparing a metal grid electromagnetic shielding optical window according to claim 10, characterized in that: The metal is selected from Cu, Ag, Au, Al or Ni.

Citation Information

Patent Citations

  • Microgel aqueous acrylic acid shell-core resin emulsion and preparation method thereof

    CN105837757A

  • Transparent conductive film, and preparation method and application thereof

    CN113284669A